2015
DOI: 10.1016/j.yhbeh.2015.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Sex, estradiol, and spatial memory in a food-caching corvid

Abstract: Estrogens significantly impact spatial memory function in mammalian species. Songbirds express the estrogen synthetic enzyme aromatase at relatively high levels in the hippocampus and there is evidence from zebra finches that estrogens facilitate performance on spatial learning and/or memory tasks. It is unknown, however, whether estrogens influence hippocampal function in songbirds that naturally exhibit memory-intensive behaviors, such as cache recovery observed in many corvid species. To address this questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 69 publications
(95 reference statements)
1
14
0
Order By: Relevance
“…In corvids [59] and finches [49], exogenous E2 interferes with hippocampal-dependent spatial memory, which is consistent with recent findings in the prefrontal cortex in aged nonhuman primates [11]. Thus, it may be that the plasticity-enhancing effects of E2 may be deleterious to the faithful initial encoding of a novel sensory stimulus [57].…”
Section: Introductionsupporting
confidence: 76%
“…In corvids [59] and finches [49], exogenous E2 interferes with hippocampal-dependent spatial memory, which is consistent with recent findings in the prefrontal cortex in aged nonhuman primates [11]. Thus, it may be that the plasticity-enhancing effects of E2 may be deleterious to the faithful initial encoding of a novel sensory stimulus [57].…”
Section: Introductionsupporting
confidence: 76%
“…Three wild adult male Western scrub-jays ( Aphelocoma californica ) were caught using Potter traps baited with peanuts in southern California (July–August 2013), and one female nestling (BB; an adult at the time of these experiments) was taken from the nest in the summer of 2012 and hand-raised (all captures were authorized under appropriate federal and state collecting permits). Birds were sexed genetically (following Griffiths et al, 1998 ), and the validity of this measure was confirmed via inspection of the gonads by Rensel and colleagues ( 2015 ). Moreover, in Rensel et al (2015) , all four scrub-jays successfully participated in caching experiments, thus indicating their acclimation to captivity.…”
Section: Methodsmentioning
confidence: 99%
“…Birds were sexed genetically (following Griffiths et al, 1998 ), and the validity of this measure was confirmed via inspection of the gonads by Rensel and colleagues ( 2015 ). Moreover, in Rensel et al (2015) , all four scrub-jays successfully participated in caching experiments, thus indicating their acclimation to captivity. Before and after our experiments, scrub-jays were housed socially with 2–4 birds per aviary (except for BB who was housed singly during a period in which she behaved aggressively toward conspecifics).…”
Section: Methodsmentioning
confidence: 99%
“…The method for improving sex-steroid extraction from plasma for RIA detailed in Newman et al (2008) has been used (cited) by researchers working primarily with bird tissues (e.g. Taves et al 2010, Shah et al 2011, Fokidis et al 2013Dickens et al 2014, Heimovics et al 2016, Prior et al 2017, Merrill et al 2019, although it has also been employed with lizard (Zena et al 2019), snakes (Rensel et al 2015), fish (Lorenzi et al 2012) and mouse (Overk et al 2013) samples. There was also some cross-over with many of the papers which cited the SPE extraction methods of Newman et al also citing Charlier et al (2010) SPE method for extracting steroids from tissues (brain) for RIA or Chao et al (2011) liquid-liquid plus SPE method for plasma and tissues extraction for ELISA.…”
Section: Forward Citation Searchesmentioning
confidence: 99%